Text Message Openings in Mandarin in the Digital Age - Lily Linai Zu (Studies in Applied Linguistics & TESOL, 2025)
This study explores the opening sequences of Mandarin text messages on WeChat, focusing on the role of the phrase zaima, meaning are you there? in English, in digital communication. While conversation openings have been widely studied in face-to-face and telephonic interactions, research on text message openings, especially in non-English languages, remains limited despite a growing dependence on digital text-based interactions through short messaging services (SMS). Using a conversation analytic (CA) framework, this study analyzes 50 instances of openings initiated with zaima from a dataset of 255 WeChat conversations, identifying two sequential environments: a unilateral conversation opening where the zaima producer moves directly to the main topic of conversation without waiting for a reply, and a bilateral conversation opening, where the zaima producer pauses for the recipient’s acknowledgement before continuing. The findings contribute to understanding how Mandarin speakers adapt conventional structures in digital openings to manage the affordances of online interactions.